Investigação sobre materiais híbridos obtidos a partir de óxido de grafeno com incorporação de sílica ou de grupos contendo fósforo - Vieira, Mariana Arpini (2018)
The reduction of graphene oxide (GO), which can be accomplished by the combination of thermal and chemical treatments, leads to the production of a material known as reduced graphene oxide (rGO); this material exhibits good electrical conductivity and, despite the presence of structural defects and chemical heterogeneity, can represent a viable and low-cost alternative to pure graphene in several applications. In the presentwork GO was produced by both Hummers and Tour methodsfrom an Li-ionbattery recycled graphite powder, varying the final content of phosphorusand sulfurby modifying the proportion of the reactants (H2SO4/H3PO4). After centrifugation the materialsweredried and concomitantly lead to thermal reduction under ambient atmosphere and at different temperatures (80, 100 and 150 °C). The products were characterized by X-ray diffraction (XRD), thermogravimetry, solid-state 13C and 31P nuclear magnetic resonance (NMR) and X-ray fluorescence. 13C NMR results show that the treatment of the materials at higher temperatures causes the progressive disappearance of the peaks associated with the oxygenated functional groups, leading to an NMR spectrum dominated by a largeresonance peak associated with sp2hybridized carbon atoms. 31P NMR results indicate that phosphorus is present in rGOsamples in the form of phosphonate groups (with P-C bonds), polyphosphoric acids (present in chains formed by the condensation of phosphate groups) and orthophosphoric acid.Furthermore, it was possible to synthesize rGO samples containing approximately 5% (m/m) of Pand 2% (m/m) of S, as stated by XRF analysis.A method of synthesizing a GO-SiO2hybrid material was also proposed, using the GOsuspension in the synthesis procedure, eliminating the drying step of the GO for its application in the preparation of the hybrid material. Results of solid-state29Si and 13C NMR,SEM, XRD and FT-IR showed that the proposed method allowed the synthesis of hybrids with different silica contents (~ 22and 46%m/m). In addition, the results of XRD, 29Si NMR, FT-IR and TG/DTG indicated the presence of nanostructured or amorphous silica and suggested the interaction of the silica particles with the GO matrixby hydrogen bonds between the silanol groups and the oxygenated functionalities of GO, and by Si-O-C bonds formed from the reaction of the carboxylic acids of the GOwith the silanol groups